Hubungan penggunaan metode concrete-pictorial-abstrack (CPA) dengan hasil belajar matematika siswa sekolah dasar - Nurkhairunnisa Siregar (Universitas Sebelas Maret, 2025)
This study aims to determine the relationship between the use of the Concrete-Pictorial-Abstract (CPA) method and the mathematics learning outcomes of elementary school students. This study uses a quantitative method with a correlational design. The study population was grade II students of SDN 200117 Padangsidimpuan, with samples selected randomly. The research instrument was a questionnaire to measure the application of the CPA method and a mathematics learning outcome test. The results of the study showed a positive and significant relationship between the application of the CPA method and students' mathematics learning outcomes. The results of the Pearson correlation test output obtained that the significance number for the relationship between the use of the CPA method and students' mathematics learning outcomes was 0.000. This means that the Sig. value (=0.000) <α (=0.05) so that there is sufficient evidence to make a decision that there is a significant relationship between the use of the CPA method and elementary school students' mathematics learning outcomes. The closeness of the relationship between the CPA method and students' mathematics learning outcomes is at a Pearson Correlation figure of 0.866. Thus, it can be interpreted that there is a strong positive relationship between the use of the Concrete-Pictorial-Abstract (CPA) method and students' mathematics learning outcomes.